Critical values for automated hemograms and peripheral blood smears: Valores críticos para hemogramas automatizados y frotis de sangre periférica - Huerto Aguilar, José L. (2022)
The report of critical values ​​is considered a necessary practice in clinical pathology laboratories, since its immediate communication determines therapeutic decisions that can save lives. The choice of critical values ​​and the way in which they are reported must be a joint decision between the laboratory specialists and the clinical professionals of each health facility, since they must be integrated into the dynamics of the services involved. Among the critical values ​​that have been chosen for this review, we have included quantitative parameters, whose processing is carried out in automated hematology analyzers, and morphological findings in peripheral blood smears, which are evaluated by trained professionals.